Gender and Factors Associated for Crime Among Prison Inmates at a Central Jail in North India - Navpreet (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background and Aims There is an increase in number of prison population over past few years. The nature of crime relates to social and economic conditions of society. To study socio-demographic factors associated with crime of prison inmates at a Central Jail in north India according to gender. Methods and Results The cross-sectional point prevalence study was conducted at Central Jail, Patiala, Punjab (India) from August 2007 to July 2008. Two hundred male inmates from different categories of crime after stratification and all sixty-five female inmates were included. The inmates were interviewed by using a pre-designed pre-tested questionnaire regarding factors associated with crime. Descriptive analysis was done, and Chi-square test was used as test of significance. There was significant difference found between educational status (p=0.00), occupational status (p=0.00), marital status (p=0.00), history of any untoward happening during childhood (p=0.00), history of conflict between family members (p=0.02) and history of alcohol/substance intake (p=0.00) of female inmates vis-à-vis male inmates. Rest of the factors were not found to be significantly different among female and male inmates. Conclusion: Factors for crime among female inmates were not much different from male inmates except for their level of education, level of occupation, marital status and family-related factors which makes female more vulnerable towards crime.